Reflections of a community-based participatory researcher from the intersection of disability advocacy, engineering, and the academy. Issue 3 (September 2017) - Raymaker, Dora M
This article uses an evocative autoethnographic approach to explore the experience of being an insider-researcher in a community-based participatory research setting. Taking a holistic perspective and using the form of narrative story-telling, I examine the dynamics between the typically marginalizing (but sometimes empowering) experience of being an autistic woman and the typically privileging (but sometimes oppressive) experience of being an engineering professional, during a time of career upheaval. Themes of motivations and mentors, adversity from social services and the academy, belonging, the slipperiness of intersectional positioning, feedback cycles of opportunity, dichotomies of competence and inadequacy, heightened stakes, and power and resistance are explored through the narrative. While primarily leaving the narrative to speak for itself per the qualitative approach taken, the article concludes with a discussion of how the personal experiences described relate both to the broader work of insider-researchers within disability-related fields, and to misconceptions about self-reflection and capacity for story-telling in individuals on the autism spectrum.